PENGUKURAN RATE KUALITAS HOTEL KOTA CIREBON DENGAN LOGIKA FUZZY METODE TSUKAMOTO - meti nurhayati (LIAISON JOURNAL OF BEST, 2022)
The growth of the Hotel rental business in the Cirebon area is increasing and resulting in more intense competition in this industry. Industrial entrepreneurs try to offer many advantages of facilities and services for customers. The previous quality measurement used a questionnaire method addressed to customers. This quality measurement method results are used for evaluation as a standard for the quality level of the Hotels. A requirement to get a good rating is the service of the Hotel in standard calculations using this method. The research was conducted to produce accurate quality calculations using fuzzy implementation using the Tsukamoto method. The working record of this method represents a monotonous fuzzy set on the membership function. Then the output is in the form of the inference value of all the rules according to the standard calculation value. The value is based on the variable type of room, facilities and rental price. Customers who want to use Hotel rental services can use this system according to their needs. Keywords: System; Hotels; Ratings; Fuzzy; Tsukamoto